Placental proteomics provides insights into pathophysiology of pre-eclampsia and predicts possible markers in plasma - Mary, Sheon; Kulkarni, Mahesh J.; Malakar, Dipankar; Joshi, Sadhana Ramchandra; Mehendale, Savita S.; Giri, Ashok P. (Journal of Proteome Research, 2017)
Pre-eclampsia is a hypertensive disorder characterized by the new onset of hypertension >140/90 mmHg and proteinuria after the 20th week of gestation. The disorder is multi-factorial and originates with abnormal placentation. Comparison of the placental proteome of normotensive (n=25) and pre-eclamptic (n=25) patients by gel-free proteomic techniques, identified a total of 2145 proteins in the placenta of which 180 were differentially expressed (>1.3 fold, p<0.05). Gene ontology enrichment analysis of biological process suggested that the differentially expressed proteins belonged to various physiological processes such as angiogenesis, apoptosis, oxidative stress, hypoxia, placental development, which are implicated in the pathophysiology of pre-eclampsia. Some of the differentially expressed proteins were monitored in the plasma by multiple reaction monitoring (MRM) analysis, which showed an increase in Apolipoprotein AI and AII in gestational week 26-30th (2-fold, p<0.01) while haptoglobin and hemopexin decreased in gestational week 26-30th and 40th week/at delivery (1.8 fold, p<0.01) in pre-eclamptic patients. This study provides a proteomic insight into the pathophysiology of pre-eclampsia. Identified candidate proteins can be evaluated further for the development of potential biomarkers associated with pre-eclampsia pathogenesis.

Early and advanced glycation end product analysis from women with PCOS on metformin - Ambekar, Aditi S.; Naredi, Nikita; Malakar, Dipankar; Vashum, Y.; Misra, Pratibha; Kulkarni, Mahesh (Reproductive Biology, 2025)
In this cross-sectional study, we have analyzed advanced glycation end products (AGEs) in the plasma and follicular fluid of women with polycystic ovary syndrome (PCOS) taking metformin during in vitro fertilization (IVF) and control women undergoing IVF. Glucose, fructose, fructosamine, carboxymethyl lysine/ arginine (CML/R) proteins, and pentosidine were measured in the plasma and paired follicular fluid. Glycated proteins were characterized by mass spectrometry. Fasting serum glucose and fructosamine were comparable; however, follicular fluid glucose and fructosamine were higher in the PCOS group, and other AGEs remained unaltered. Fructose was lower in both serum and follicular fluid from the PCOS group. A positive correlation between some of these AGEs and sugars estimated was observed. Glucose and fructosamine in the follicular fluid correlated with the antral follicle count. The number of glycated peptides identified in the PCOS group by mass spectrometry was more. Glycated K75, K402 amino acid residues of albumin were detected in the PCOS group only. Additionally, some proteins involved in steroidogenesis and oocyte maturation as well as transporters, and extracellular matrix proteins, were found to be glycated in the PCOS group, which may affect their function. Elevated glucose and fructosamine in the follicular fluid of the PCOS group may contribute to abnormal folliculogenesis. The glycation of albumin should be validated in more samples to be considered as a marker for PCOS diagnosis.
Keywords: Carboxymethyl lysine; Fructosamine; fructose; glucose; Pentosidine; Polycystic ovary syndrome